School for Parents. (Journal of Parents and Teachers, 2025)
The article focuses on the importance of addressing drug use, both legal and illegal, in parent education programs. However, the problem goes deeper, as those parents who advise their children against smoking or drinking are often the first to consume these substances themselves. Furthermore, the article includes a planning section covering methodology, objectives, resources, and activities to effectively develop a parent education program.
Keywords: parents education program; consumption; drugs; planning